2013
DOI: 10.3382/ps.2012-02727
|View full text |Cite
|
Sign up to set email alerts
|

Extra-phosphoric effects of superdoses of a novel microbial phytase

Abstract: An experiment was conducted to evaluate the influence of a novel microbial phytase on broiler performance from d 0 to 42 and tibia ash at d 21. Male Cobb 500 broilers (n = 2,016) were fed 1 of 7 experimental diets: positive control (PC) formulated to meet or exceed nutrient recommendations; PC plus dicalcium phosphate (PC+DCP) formulated to provide Ca and P at 0.10% above the PC; PC plus 500 U/kg of microbial phytase (PC+500); negative control (NC) with Ca and P reduced from the PC by 0.16 and 0.15%, respectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
40
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(45 citation statements)
references
References 18 publications
2
40
0
3
Order By: Relevance
“…Any negative effects of this reduction were most likely muted by enhanced digestibility of phytate P. Such effects have been noted elsewhere. Indeed, Walk et al [ 27 ] reported no deterioration in FI, FCR or BWG when 42 or 49-d-old broilers were fed corn-soybean diets which were apparently deficient in Ca and available P by 0.16%, and 0.15% respectively, as compared with the positive control diet. In that study, however, younger birds (0–21 d) did exhibit reduced BWG without changes in FI and FCR, suggesting that young chickens may be more susceptible to a marginal P deficiency than older birds [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Any negative effects of this reduction were most likely muted by enhanced digestibility of phytate P. Such effects have been noted elsewhere. Indeed, Walk et al [ 27 ] reported no deterioration in FI, FCR or BWG when 42 or 49-d-old broilers were fed corn-soybean diets which were apparently deficient in Ca and available P by 0.16%, and 0.15% respectively, as compared with the positive control diet. In that study, however, younger birds (0–21 d) did exhibit reduced BWG without changes in FI and FCR, suggesting that young chickens may be more susceptible to a marginal P deficiency than older birds [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, Walk et al [ 27 ] reported no deterioration in FI, FCR or BWG when 42 or 49-d-old broilers were fed corn-soybean diets which were apparently deficient in Ca and available P by 0.16%, and 0.15% respectively, as compared with the positive control diet. In that study, however, younger birds (0–21 d) did exhibit reduced BWG without changes in FI and FCR, suggesting that young chickens may be more susceptible to a marginal P deficiency than older birds [ 27 ]. However, in our studies, there were no differences in BWG and FCR between the positive and negative controls from 1–14 d and 1–42 d of age, suggesting Ca and P were not limiting in either diet.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Poultry represents the most efficient form of terrestrial animal protein: a modern commercial chicken can gain 3.48 kg in body weight by consuming just 6.37 kg of feed in 49 days (Walk et al, 2013). Although much of this efficiency is due to selective breeding and management practices such as supplementation of feed with exogenous enzymes, the importance of the gastrointestinal microbiome for poultry nutrition is increasingly being recognized.…”
Section: Importance Of the Gastrointestinal Microbiome For Gut Healthmentioning
confidence: 99%
“…Walk et al, 2013). In addition, there is little research comparing the effectiveness of genetically modified transgenic phytase corn (TPC) to commercially available phytase enzymes.…”
mentioning
confidence: 99%